(untitled) (Bangladesh Journal of Medical Science, 2012)
Background and Objectives: Pregnancy is the physiological process in which progressive anatomical, physiological and biochemical changes occur. Secretion of different hormones during pregnancy is responsible for maternal adaptation to the increasing demand of the growing fetus. The present study was aimed to evaluate serum calcium and phosphate status in normal pregnant women in different trimesters. Materials and Methods: A total number of 140 subjects, age range 20-40 (yrs) were recruited in the study which includes 100 normal pregnant women termed as study group (Group B) and 40 healthy women without pregnant (Group A), served as Control. Group B subjects were subdivided into Group B1 (n=12), Group B2 (n=30) and Group B3 (n=58) on the basis of duration of pregnancy- 1st, 2nd and 3rd trimesters respectively. Calcium was measured by CPC (photometric method for Ca) and serum phosphate by colorimetric method. Statistical analysis was done using SPSS for Windows, Version 10. Unpaired Student’s -’t’ test performed to calculate statistical differences between groups. Results: Age (yrs) (mean±SD) and BMI of the pregnant women in different groups did not show statistical difference. Serum calcium (mean±SD) levels in the 1st (p=0.0001) and 2nd (p=0.02) trimester was significantly higher compared to the Controls. In 3rd the value was significantly lower (p=0.015) compared to the Controls and of 1st and 2nd trimesters (p=0.001). Serum phosphate (mean±SD) levels in three trimesters did not show statistical significant difference compared to the Controls and among the pregnancy groups. Conclusion: The data concluded that serum calcium level was lower during third trimester of the study subjects which may be explained by the fact of increased demand of the growing fetus and exposing the mother at risk of complications related to low serum calcium. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11732 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12